2020
DOI: 10.1088/1757-899x/746/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of MAO Film Layer on LY12 Aluminum Alloy Surface in Sodium Hexametaphosphate Solution

Abstract: Aluminum alloy is widely used in power grids to solve the problem of aluminum excess and copper deficiency. The MAO film is prepared by micro-arc oxidation on LY12 aluminum alloy with phosphate electrolyte. The growth rate of film layer in different treatment time is studied and the variation trend of film in growth and outward growth was carried out. Finally, the morphology and composition of the film were tested by SEM and EDS. The results show that the initial growth of micro-arc oxidation is slow, mainly g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Plasma electrolytic oxidation on aluminum alloys in electrolytes containing (NaPO 3 ) 6 showed that the oxide coatings had a porous microstructure with fine pores, which form craters on the surface of the alloy resulting from the remelting events in the discharge channels and the growth trend of the coatings was almost linear [31].…”
Section: Microstructure and Chemical Analysis 311 Cross Sectional Ima...mentioning
confidence: 99%
“…Plasma electrolytic oxidation on aluminum alloys in electrolytes containing (NaPO 3 ) 6 showed that the oxide coatings had a porous microstructure with fine pores, which form craters on the surface of the alloy resulting from the remelting events in the discharge channels and the growth trend of the coatings was almost linear [31].…”
Section: Microstructure and Chemical Analysis 311 Cross Sectional Ima...mentioning
confidence: 99%